Translation of Culture/Culture in Translation: A Postcolonial Perspective. - BOUREGBI, Salah (Annals of Philosophy, Social & Human Disciplines, 2023)
The postcolonial theory of translation has emerged as a pattern of systems that enables a translator to re-conceptualize and revisit texts and redirect his attention to the dichotomy of Subject/Object relationships far from the hegemonic language of the logocentric Europe. Reproducing a text through rewriting is subjugating it to the will and intention of the local - the margin / the Other. Culture and Translation are two very polemical elements in perpetual tension due to the amount and the degree of reliability of the transfer from the source text to the target. Many studies have been made to find an issue and an adequate theory of translation to transfer the culture of the source to the target smoothly. However, these studies are not as effective as they might be because translation is rather a maneuvering and a biased manipulation of the text, and what is transferred as culture is just what is conceived or rather perceived by the translator whose background is the cornerstone of his rendering. Postcolonial theory has come in recourse to translation: its basic strategy is translation through dualism and alterity. It is a kind of H. Bhabha's Third Space or Bill Ashcroft's Rewrite: revisiting the text and its culture through the Other's Eye / "I." But this Rewrite pattern of translation needs more adequate mechanisms to transfer one culture into another language and avoid the constraints imposed by the power of the Subject that hinders the reading, rethinking, and interpreting of the text and is, frequently, hovering around and behind any translation activity.